Explaining strategic disinterment: Forensics and the reconstruction of the missing in Cyprus - Mikellide, Maria; Lyritsas, Romanos; Ioannidis, Nikandros; Kovras, Iosif (My University, 2024)
The paper investigates the phenomenon of ‘strategic disinterment’ in Cyprus, namely the purposeful and selective destruction of primary graves and removal of remains of missing persons to unknown secondary burial sites. Our examination of why violent actors invest valuable resources to exhume victims from the original burial location, even when they no longer pose a security threat, has significant theoretical and methodological implications. First, it pushes the boundaries of our understanding of violence by challenging the assumption that violent actors target only the living. Second, it innovates methodologically by introducing the use of forensic data to explain the strategic logic of selective removal of remains of victims from original grave sites in Cyprus. By exploring the interplay between temporal, spatial, demographic, and political considerations and analysing variables that may explain strategic disinterment, we make informed inferences about the possible drivers of grave selection. We argue the decision of armed groups to engage in strategic disinterment in Cyprus was shaped by a set of two factors. On the one hand, they were ‘pushed’ by the degree of perceived accountability associated with specific graves that concealed incriminatory evidence of heinous crimes. On the other hand, their capacity to organize sophisticated operations, such as mass-scale reburials, was crucial. Only actors with the capacity and attentive to (international) accountability norms were likely to engage in strategic disinterment.
Keywords: Graves; Forensic data; Disappearances; Repertoires of violence; Cyprus conflict